Investigation on Horizontal and Vertical Traveling Ionospheric Disturbances Propagation in Global‐Scale Using GNSS and Multi‐LEO Satellites - Xiaodong Ren; Dengkui Mei; Hang Liu; Xiaohong Zhang (Space Weather)
Abstract Global Navigation Satellite System (GNSS) observations from worldwide ground‐based stations have been extensively used in traveling ionospheric disturbance (TID) detections. However, these observations primarily cover land area, thus causing a challenging problem of interpreting the global propagating characteristics of large‐scale TIDs (LSTIDs), especially over the ocean area. Meanwhile, Total Electron Content (TEC) values derived from ground‐based GNSS signals propagating through the whole ionosphere have an integral character, and we were unable to obtain the propagation and dissipation of TIDs in the vertical direction using solely ground‐based GNSS TEC data. In this study, apart from ground‐based GNSS observations, in situ data and GNSS observations from precise orbit determination receivers on board Low‐Earth‐Orbit (LEO) satellites were integrated for the first time for the global large‐scale TID investigation during the St. Patrick's Day geomagnetic storm. Through experiments, we found that LEO satellite observations effectively compensate for areas where the TIDs cannot be detected by sparse ground‐based GNSS data, particularly over the ocean and polar areas. The space‐borne TEC and in situ data provided the new observational evidences of LSTIDs propagating up to the topside ionosphere during the 17 March 2015 storm, serving as great supplements to ground‐based GNSS data. Combining space‐borne GNSS data with in situ data at various orbit altitudes offers opportunities for theoretical studies of TID propagations at different ionospheric heights and for a better understanding of the complex coupled processes of the TIDs with the geospace environment.